Anatomic-Physiological Eatures of Dogs - Khudaynazarova, N. E.; Haydarova, S. R. (American Journal of Biomedicine and Pharmacy, 2025)
The nucleus is the most important part of the cell, participating in all its vital processes. The bones of puppies and young dogs are very elastic due to the large amount of moisture and organic substances – collagen fibers. With age, bones, losing water and organic components, become more fragile and brittle.